2014
DOI: 10.1155/2014/589587
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Central Europe

Abstract: Little published information is available regarding epidemiological data on vitamin D status in the large geographical region of Central Europe (CE). We searched the journal literature with regard to 25(OH)D concentrations among community-dwelling or healthy people living in CE. 25(OH)D concentrations varied by age, season, study sample size, and methodological approach [i.e., 25(OH)D assay used]. Concentrations of 25(OH)D in CE appeared lower than 30 ng/mL, and the magnitude of hypovitaminosis D was similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
4
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 50 publications
(44 reference statements)
15
110
4
14
Order By: Relevance
“…Our results reflect those reported in an Italian study, which found that median vitamin D serum levels >25 ng/ ml were similar in the HIV mono-infected, HIV/HCV co-infected and healthy controls [29]. Moreover, in a recent, large study on a general healthy population in Central Europe, Pludowski et al [30] reported an average vitamin D concentration of >30 ng/ml. However, since the Hormone Foundation's Patient Guide to Vitamin D Deficiency suggests that patients with chronic (long-term) liver disease are at high risk of deficiency [31], further randomized controlled trials are warranted to determine what level of vitamin D insufficiency and deficiency places an individual at risk for cirrhosis evolution.…”
Section: Discussionsupporting
confidence: 89%
“…Our results reflect those reported in an Italian study, which found that median vitamin D serum levels >25 ng/ ml were similar in the HIV mono-infected, HIV/HCV co-infected and healthy controls [29]. Moreover, in a recent, large study on a general healthy population in Central Europe, Pludowski et al [30] reported an average vitamin D concentration of >30 ng/ml. However, since the Hormone Foundation's Patient Guide to Vitamin D Deficiency suggests that patients with chronic (long-term) liver disease are at high risk of deficiency [31], further randomized controlled trials are warranted to determine what level of vitamin D insufficiency and deficiency places an individual at risk for cirrhosis evolution.…”
Section: Discussionsupporting
confidence: 89%
“…In our study we found that the median serum 25(OH)D concentration in AMI patients was 7.1 (2.3-13.3) ng/mL and this value was below the recommended reference range for healthy population (Table 2) [10]. Detailed analysis of 25(OH)D levels revealed that 53 (89.8%) patients had vitamin D below 20 ng/mL, and six (10.2%) patients had suboptimal 25(OH)D levels (between 20 ng/mL and 30 ng/mL).…”
Section: Resultscontrasting
confidence: 55%
“…Our results are taken in relation to the guidelines prepared for the population of Central Europe. According to the recommendations of prophylaxis of vitamin D deficiency in Poland, the concentration of vitamin D < 20 ng/mL has been treated as VDD, and levels between 20 ng/mL and 30 ng/mL are characterised as suboptimal, with insufficient vitamin D supply to the body [10,11]. Additionally, we can confirm that the distribution of VDD in cardiovascular patients is in concordance with the previous investigation by Goleniewska et al [4]; nevertheless, we did not check the association between the severity of coronary lesions and vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a general population, daily sunlight exposure influences vitamin D serum concentrations, leading to strong seasonal intra-and inter-individual variability [3,4]. It is not self-evident, though, that these results can be transferred to HIV-infected subjects: for patients on anticonvulsant drugs (which are considered to interfere similarly to ART [1]) and patients with hyperparathyroidism (which was found to occur secondary to ART with tenofovir disoproxil fumarate [5,6]) a loss of seasonality has been described [7,8].…”
Section: Seasonal Variations In Vitamin D Levels In Hiv-infected Patimentioning
confidence: 99%